Mengungkap Pengaruh Label Halal, Kualitas Pelayanan, Bukti Fisik, dan Promosi Media Sosial terhadap Keputusan Pembelian Mie Gacoan di Semarang - Kusuma, Danny Arya; Putra, Febrianur Ibnu Fitroh Sukono; Tri Esti Rahayuningtyas (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The study aims to determine the effect of halal labeling variables, service quality, physical evidence, and social media promotion on purchasing decisions for gacoan noodles in Semarang City. Approach: This study uses a quantitative approach method Research Finding: service quality, physical evidence, and social media promotion significantly affect purchasing decisions for gacoan noodles in Semarang City. Meanwhile, the halal label variable has no significant effect. Theoretical contribution/Originality: The novelty of this research lies in the finding that the halal label, although generally considered important in the Muslim consumer market, does not have a significant influence in the context of fast food cuisine favored by students. This provides a new perspective in understanding young consumers' preferences in Indonesia, especially in the fast food industry. Practitioner/Policy implication: Focusing on improving service quality, physical evidence, and social media promotion, as well as considering customer preferences regarding halal labeling, Mie Gacoan can increase the attractiveness and competitiveness of their products in the Semarang city market Research limitation: This research only focuses on halal labeling, service quality, physical evidence, and social media promotion.